(untitled) (Global Journal of Science Frontier Research, 2016)
Root crops in general and taro in particular are the main food crop, the only and livelihood dependant highly productive and multifunctional crop that used for as livestock feed supplement and human food item in southern Ethiopia, but its role in food and nutritional security had not been studied and well documented, consequently less attention was given in development agenda of the country. Hence, the study was aimed to undertake investigation in livelihood role Improved taro variety that helps in generation information on role of improved taro for farming communities in the district. The study was undertaken in Kindo koisha Woreda and Duguna Fango Woreda of Wolaita zone Administrative. The study revealed that the contribution of taro on the overall livelihoods of the beneficiaries is significantly high. The impact of Boloso-1-Taro ranges from saving life to reduction of migration and school dropout rates. It has also diversified income for the beneficiary farmers in general and able to generate income from selling taro production that empowered women and changed the family’s living status.